2008
DOI: 10.1001/jama.299.8.901
|View full text |Cite|
|
Sign up to set email alerts
|

Switching to Another SSRI or to Venlafaxine With or Without Cognitive Behavioral Therapy for Adolescents With SSRI-Resistant Depression

Abstract: DOLESCENT DEPRESSION IS A common, chronic, recurrent, and impairing condition that accounts for a substantial proportion of the disability and mortality incurred in this age group. 1,2 Untreated depression results in impairment in school, interpersonal relationships, occupational adjustment, and in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
466
4
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 617 publications
(486 citation statements)
references
References 71 publications
9
466
4
7
Order By: Relevance
“…Fischer (2013) ha iniciado un ECA para evaluar la efi cacia de este programa, que prevé acabar de recoger datos a fi nales del 2014. El Treatment of SSRI-Resistant Adolescent Depression (TORDIA; Brent et al, 2008) es el único estudio que evalúa de forma separada las autolesiones no suicidas de aquellas con intencionalidad suicida. Incluye adolescentes de 12 a 18 años con diagnóstico de trastorno depresivo mayor y que no tienen respuesta a un inhibidor selectivo de la recaptación de la serotonina (ISRS).…”
Section: Terapias Cognitivo-conductualesunclassified
See 1 more Smart Citation
“…Fischer (2013) ha iniciado un ECA para evaluar la efi cacia de este programa, que prevé acabar de recoger datos a fi nales del 2014. El Treatment of SSRI-Resistant Adolescent Depression (TORDIA; Brent et al, 2008) es el único estudio que evalúa de forma separada las autolesiones no suicidas de aquellas con intencionalidad suicida. Incluye adolescentes de 12 a 18 años con diagnóstico de trastorno depresivo mayor y que no tienen respuesta a un inhibidor selectivo de la recaptación de la serotonina (ISRS).…”
Section: Terapias Cognitivo-conductualesunclassified
“…El entrenamiento en solución de problemas y en habilidades sociales fueron los componentes más efi caces en los datos analizados (Kennard, 2009). A pesar de esto, no se encontraron diferencias en la ratio de episodios de NSSI (Brent et al, 2008).…”
Section: Terapias Cognitivo-conductualesunclassified
“…32 However, of patients who do not respond to fluoxetine, 50% will respond to another SSRI antidepressant. 33 In the UK, sertraline and citalopram are regarded as second-line SSRIs for child and adolescent depression 11 (see Table 2), and this has some research support. 34 Citalopram is associated with QT prolongation and so individuals known to have cardiac abnormalities, or at risk of these, should have an ECG carried out prior to using this drug.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…A third-line drug would be venlafaxine which may be beneficial, 33 but the side effects result in a high level of non-adherence. The antidepressants frequently used in the USA are also included in Table 2 given the mobility of young people from the USA to Europe.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…5 In the Treatment of Adolescent Depression Study, 6 the rate of suicidal events was lower in the combination of antidepressant and CBT than in medication alone; however, in other clinical trials of more severely or chronically depressed youth, no protective effect was found for combination treatment. 6,7 No relation has been established among dosage, adherence pattern, medication type, and risk for events, and while some promising pharmacogenetic findings have been reported, there is currently no clinical applicability of these findings.Several hypotheses, all unproven, have been advanced to explain the increased rate of suicidal events in antidepressant-treated patients, compared with those on placebo. These have included induction of akathisia, disinhibition, increasing energy of the patient to the point where he or she can actually make an attempt, induction of mania or a mixed state, or withdrawal from medication as a result of nonadherence, with induction of dysphoria and suicidality.…”
mentioning
confidence: 99%